Nordic checklist food contact materials: Declaration of compliance and supporting documentation - Mikkelsen, Bjørg (TemaNord, 2015)
Documentation of compliance with the legislation is a corner stone in the control of food contact materials (FCM). In-house control is an important pre-requisite to limit contamination from FCM and shall be based on the declaration of compliance and supporting documentation at the responsible business operators in the supply chain. The goal of this project was to develop a Nordic checklist on documentation of compliance for FCM. The Nordic checklist contains several templates. The different templates provide check points on the minimum requirements for a declaration of compliance for all types of materials. The templates are meant to be used by industry and trade as guidance for drafting a declaration of compliance. Furthermore, the check lists are also meant to be tools for the public food and FCM inspection.